2019
DOI: 10.1007/s11104-019-04012-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitrogen fixation from free-living organisms in soil and leaf litter of two tropical forests of the Guiana shield

Abstract: Background and aims Biological fixation of atmospheric nitrogen (N 2) is the main pathway for introducing N into unmanaged ecosystems. While recent estimates suggest that free-living N fixation (FLNF) accounts for the majority of N fixed in mature tropical forests, the controls governing this process are not completely understood. The aim of this study was to quantify FLNF rates and determine its drivers in two tropical pristine forests of French Guiana. Methods We used the acetylene reduction assay to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 91 publications
1
32
0
Order By: Relevance
“…The response to the fertilization treatments was rapid (≈1 month; Figures 3A, 4) but relatively transient for +N and +P, compared to +NP. Although soils in French Guiana have very low concentrations in available P (Grau et al, 2017;Van Langenhove et al, 2019) compared with many southern and western Amazonian soils [i.e., 10 times lower for Acrisols (Quesada et al, 2010)], our results showed a higher CO 2 efflux in +NP fertilized soils than in +N or +P alone, suggesting co-limitation of N and P. In concordance, previous studies on the same tropical French Guianese soils have demonstrated the positive impact of N and P additions on faunal decomposers and litter decomposition rates (Barantal et al, 2012;Fanin et al, 2015Fanin et al, , 2016 but no effects when N or P were added alone. This co-limitation of soil respiration contrasts with findings from fertilization experiments in tropical lowland forests in Panama (Kaspari et al, 2008), Costa Rica (Cleveland and Townsend, 2006), and Hawaii (Hobbie and Vitousek, 2000), which showed a significant and positive effect of N or P addition on soil organic matter decomposition.…”
Section: Combined Effects Of Fertilization and Drought On Soil Co 2 Ementioning
confidence: 99%
“…The response to the fertilization treatments was rapid (≈1 month; Figures 3A, 4) but relatively transient for +N and +P, compared to +NP. Although soils in French Guiana have very low concentrations in available P (Grau et al, 2017;Van Langenhove et al, 2019) compared with many southern and western Amazonian soils [i.e., 10 times lower for Acrisols (Quesada et al, 2010)], our results showed a higher CO 2 efflux in +NP fertilized soils than in +N or +P alone, suggesting co-limitation of N and P. In concordance, previous studies on the same tropical French Guianese soils have demonstrated the positive impact of N and P additions on faunal decomposers and litter decomposition rates (Barantal et al, 2012;Fanin et al, 2015Fanin et al, , 2016 but no effects when N or P were added alone. This co-limitation of soil respiration contrasts with findings from fertilization experiments in tropical lowland forests in Panama (Kaspari et al, 2008), Costa Rica (Cleveland and Townsend, 2006), and Hawaii (Hobbie and Vitousek, 2000), which showed a significant and positive effect of N or P addition on soil organic matter decomposition.…”
Section: Combined Effects Of Fertilization and Drought On Soil Co 2 Ementioning
confidence: 99%
“…(2006) in a review of the nitrogen cycle in tropical and temperate savannas. The available P contents are described as a limiting factor to N 2 fixation in P-deficient soils in the tropics ( Bustamante et al., 2006 ; Van Langenhove et al., 2019 ) and could be critical to activate genes for the nitrogenase synthesis ( Stock et al., 1990 ). However, although the increase in P availability is usually described to increase N 2 fixation, the free-living diazotrophs could perform BNF over a broader range of phosphorus supply or accessibility than symbionts ( Smercina et al., 2019 ), suggesting other controls to nifH abundance for this group.…”
Section: Discussionmentioning
confidence: 99%
“…For the southeastern Amazon and Belize, we plot the average wet season ARA rates in the litter with the canopy C:N ratio instead of litter C:N. All other ARA rates are associated with the specified substrate: canopy, litter, and soil. For ARA rates and substrate stoichiometry, data are from Belize (Winbourne et al 2017), Costa Rica (Reed et al 2013), French Guiana (Van Langenhove et al 2020), Panama (Barron et al 2009, Wurzburger et al 2012), Puerto Rico (Cusack et al 2009), and southern China (Zheng et al 2018). Sources for soil inorganic nitrogen concentrations are from Hall and Matson (2003), Funk (2005), Yavitt et al (2009), Sullivan et al (2014), Winbourne et al (2018), Brookshire et al (2019), Taylor et al (2019), Osborne et al (2020), Van Langenhove et al (2020), and Wong et al (2020 b ).…”
Section: Discussionmentioning
confidence: 99%